2014
DOI: 10.22146/gamaijb.5468
|View full text |Cite
|
Sign up to set email alerts
|

Technology Readiness and E-Commerce Adoption among Entrepreneurs of SMEs in Bandung City, Indonesia

Abstract: Abstract:The emergence of internet-based electronic commerce offers considerable opportunities for companies to expand their customer base, enter new product markets, and rationalize their business. The Indonesian government has initiated and implemented a series of plans and activities to promote technology use to increase SMEs' performance. Despite such efforts, technology adoption rate are still low. Therefore, it is important to understand the factors affecting an entrepreneurs' decision on internet adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
3
39
1
4
Order By: Relevance
“…Age was significantly associated with SSK adoption and independent decision-making for mobile banking, while education significantly affects OL regarding ATMs. All these relations are found to be more consistent with the findings of past adoption studies (Astuti & Nasution, 2014;Rogers, 1995;Venkatesh, Sykes, & Venkatraman, 2014). …”
Section: Other Findingssupporting
confidence: 88%
“…Age was significantly associated with SSK adoption and independent decision-making for mobile banking, while education significantly affects OL regarding ATMs. All these relations are found to be more consistent with the findings of past adoption studies (Astuti & Nasution, 2014;Rogers, 1995;Venkatesh, Sykes, & Venkatraman, 2014). …”
Section: Other Findingssupporting
confidence: 88%
“…E-Commerce is defined as a channel for any type of transaction, including offering products and services through the Internet, which, despite its advantages, has not yet managed to persuade a greater proportion of users to carry out transactions through this means of shopping [23]. In this regard, several studies have shown that the rate of consumer adoption for e-commerce is low in emerging economies and in micro, small and medium sized enterprises (SMEs) compared to developed countries [10], [18], [54], [70], [73], [99], [141]. Therefore, it has been considered important to conduct studies that examine the trends and developments in the identification of factors that encourage the adoption of e-commerce.…”
Section: Adoption Factors Of E-commercementioning
confidence: 99%
“…However, although it has become a source of competitive advantage due to the possibilities offered to both buyers and sellers, its use, especially in emerging economies, is limited [52]. The main advantage mentioned by the authors in the use of electronic commerce relates to the opportunity that it provides for companies to expand their number of customers [18] and its potential to become a medium to boost micro, small and medium sized enterprises--which represent a source of economic growth for many countries [70], [102]. In the United States, for example, it has become a transactional medium used for business by nearly 40% of the third of the population [55].…”
mentioning
confidence: 99%
“…Although there are many potential advantages of e-commerce (see e.g. [1], [4], [42], [58], the incorporation of ecommerce by SMEs remains limited. In Chile, for example, there is a big gap between the adoption rate of large companies and their small counterparts.…”
Section: Innovativenessmentioning
confidence: 99%